Tinjauan Literatur: Hubungan antara Keragaman Pangan dengan Stunting pada Balita: Literature Review: The Relationship between Dietary Diversity with Stunting in Underfive Children - Ulfa Al Uluf; Alfadhila Khairil Sinatrya; Siti Rahayu Nadhiroh (Universitas Airlangga, 2023)
Background: Stunting is a global health problem in children under five. Failure to grow, develop, and metabolize due to stunting can threaten a child's future. The diversity of food consumed daily can be a factor affecting the incidence of stunting. Objectives: This literature aimed to determine the relationship between dietary diversity and the incidence of stunting in children under five. Discussion: Ten articles met the criteria, with six articles stating that there was a relationship between dietary diversity and stunting, stating that the more diverse the food groups consumed, the less probability of children under five getting stunted. Conclusions: This study concludes that dietary diversity is related to the incidence of stunting in children under five. This research can be used as a reference to maximize the availability of dietary diversity, especially in the locus area of stunting.